Estrategias de marketing en la Consultoría RD en la ciudad de Babahoyo en el periodo 2023 - Bastidas Arambulo, Kerly Daniela (2024)
This case study consists of an analysis of the marketing strategy. In the RD consultancy that is dedicated to providing services with experience in tax issues, opening bank accounts and Western Union payments in the city of Babahoyo. It was formed through the research line “Financial Management, Administration, Taxation, Audit and Control” and is part of the “Marketing and Commercialization” subline. This work applies research methods to the different needs of clients to find out their preferences and the hypothetical deductive procedure that allows us to analyze the data obtained and create an argument about it. In addition, the following research techniques were used: interview with the owner of the company. To develop the work, it was necessary to identify the existing weak points in the company, such as deficiencies in marketing strategies, lack of advertising and sales promotion, which is why the company wants to optimize the marketing process.